Understanding divergence in Channa striata : A genetic and morphological approach / Song Li Min - Song, Li Min (2012)
The snakehead murrel, Channa striata, or “Haruan” in Malaysia, is well known with its pharmaceutical purpose and hence is extensively studied for its biochemical compound involved in medication while its knowledge on population structure is poorly inventoried. This study was conducted to characterize the naturally occurring populations of C. striata using both molecular and morphological approaches. These specimens were extensively caught from wide geographical range across Malaysia in the aim to propose spatial conservation assessment on this species as well as to investigate the possible hidden cryptic species of C. striata in Malaysia. Our data evidence the presence of variation in C. striata with the molecular divergence pattern is not congruent to the morphological divergence pattern. In this study, for example, population from Negeri Sembilan and Johor were genetically alike; however, these two populations together with population from Pulau Pinang were characterized by a unique head size in relation to others indicating that the physical habitat heterogeneity is probably the trait deformity agents. This suggests that environment conditions such as food source, changes in water temperature, contaminated organic compound and other possible environment factors will influence the development of fish trait which need not correlated with underlying genetic differences. Besides, our molecular data on DNA barcoding approach did not revealed possible cryptic species of C. striata among all studied sites in Malaysia although this species shows high population divergence in South-East Asia. This is supported by a monophyletic divergence pattern of C. striata reflected in the phylogenetic tree inferred using both NJ and Bayesian inference method with high statistical support. Nevertheless, another supportive results of low intraspecies genetic distance (0.60%) compared to its con-generic distance (1.70%) and this intra-species variation (0.60%) was less than the threshold value (1.60%) under Hebert’s et al., 2004a 10X benchmark, strongly suggest that there is no possible existance of hidden cryptic species at the present study. The molecular mtDNA data in this research study were able to illustrate the historical dispersal pattern of C. striata. Although physical barrier separation tends to cause population divergence, for example, unique haplotype was found at populations in the central division of Peninsular Malaysia which are separated by physical barrier; however, the historical coalescence of this candidate species was mainly explained by geomorphologic structure and ancient natural climatic changes that affect the area of expose land mass. The unexpected overlapping haplotype distribution and nonsignificant population difference between the mainland and the island of Borneo are most probably explained by the incident of historical connection during Pleistocene Epoch. The understood population divergence pattern revealed in this study provides valuable information for subsequent spatial conservation planning based on different aspects and also informative to ecologist to further study the water quality on this candidate’s morphology as C. striata tends to be a potential bio-marker in respond to the changes in dissolved chemical compounds.